Building type basics for elementary and secondary schools - Perkins, L. Bradford (Building type basics, 2010)
Written by an experienced architect, Building Type Basics for Elementary and Secondary Schools explains key elements of school design through descriptive diagrams and photos. This comprehensive guide provides the foundation of architectural design of elementary and secondary schools.